Integrated Pest Management Policy and Treatment Options for University Housing - Kevyn J. Juneau; Jennifer L. Gillett-Kaufman; Norman C. Leppla; Kirk W. Martin; A. Wayne Walker (EDIS, 2011)
The purpose of this manual is to train pest management technicians of the UF Department of Housing and Residence Education in integrated pest management (IPM). It includes the DOHRE IPM policy, specific IPM objectives, responsibilities of the DOHRE Senior IPM Technician, a flow chart of IPM actions, and requirements for using pesticides and associated recordkeeping. Pest-specific IPM options are provided for ants; bed bugs; bees and wasps; birds and bats; booklice, silverfish, and earwigs; cockroaches; flies; rodents; stored product pests; termites; and weeds. Selected references are provided, and there are forms for assuring service, pest surveillance, and record keeping. This 42-page training manual was written by Kevyn J. Juneau, Jennifer L. Gillett-Kaufman, Norman C. Leppla, Kirk W. Martin and A. Wayne Walker and published by the UF Department of Entomology and Nematology, February 2010.